PENGEMBANGAN MEDIA MOTION COMIC UNTUK MENINGKATKAN BERPIKIR ALJABAR SISWA MI AS SA’ADAH PADA ERA KENORMALAN BARU - Awiria Awiria; Dariyanto Dariyanto (Universitas Sarjanawiyata Tamansiswa, 2022)
Algebraic thinking is one of the skills needed at this time. Problem-solving activities dominate the ability to think algebraically, but in this case, the solution is not yet known. The solution that is possibly done can be through appropriate examples and self-discovered methods. Previous research found obstacles in algebraic thinking, namely epistemology obstacles, didactical obstacles, and conceptual obstacles. In addition, there is currently a lack of studies on learning media used to familiarize students with algebraic thinking since MI. This research aims to develop motion comic learning media based on digital literacy. The method used was Research and Development (R&D), which involved 25 students of MI class IV. This study yielded design principles of digital literacy-based motion comic learning media that have mathematical material content whose context is adjusted to the learning process in the new normal era.